Proses Administrasi Kredit Back To Back Loan Dalam Mengurangi Rasio Non Performing Loan (NPL) Di Bank BJB Kantor Cabang Sukajadi - asbatian nur fadirohim; Chandra Hendriyani (Jurnal Sekretaris dan Administrasi Bisnis, 2021)
The banking world has never been separated from people's lives today. The many features offered do not escape from the target of society. Including credit facilities that are always owned by every conventional bank. One type of credit is a Back To Back Loan credit at BJB Bank. To get the facility, prospective customers must go through several stages, including credit administration to find out the level of the ability of prospective borrowers to make installment payments each month to avoid Non Performing Loans (NPL). Because high NPL can disrupt the liquidity of the banks. The purpose of this study is to determine the administrative process undertaken by prospective debtors when applying for Back To Back Loan credit at BJB Bank. The research method used is qualitative with a descriptive approach. Data collection techniques used were the study of literature from journals, secondary data and interviews to the credit administration section of the branch unit. The results showed that the Back To Back Loan credit administration process carried out by BJB Bank has proven to be able to reduce the number of bad loans or NPLs so that the credit movement can run stably.